The Ethics of Vaginal Birth after Cesarean - Charles, Sonya (The Hastings Center report, 2012)
The decline in providers and facilities that will allow a trial of labor after cesarean forces many women to choose a repeat cesarean. The choice is frequently not much of a choice, however, since the full range of options are often not on the table. This limited “choice” violates obstetricians' obligations both to respect patients' autonomy and to offer them good care. There has been a vigorous but so far not very fruitful debate in the last few years about the lack of access to a trial of labor after cesarean. Some recently released documents express concern about the limited access women have to clinicians and facilities willing to offer a trial of labor after cesarean. But access is likely to remain a problem for the foreseeable future.